O Suporte Básico de Vida durante a Prática Deliberada em Ciclos Rápidos sob a ótica de estudantes universitários - Nalin, Gabriela Wicher (2023)
To analyze the perceptions of university students in Basic Life Support during Deliberate Practice in Rapid Cycles (PDCR). Method: descriptive-exploratory study, using a qualitative approach. The study scenario was developed at the Health Simulation Unit (USS) of the Federal University of São Carlos (UFSCar), located in the city of São Carlos. The population of this study was made up of 29 students regularly enrolled in undergraduate courses at UFSCar during the period established for data collection, with a higher prevalence of female participants (75.86%), aged between 21 and 22 years ( 34.47%). Data were collected through semi-structured interviews, which combine open and closed questions, carried out by two previously trained collaborating researchers who did not participate in the PDCR phase. The interviews were transcribed in full and stored in Google Docs, in which the analysis was carried out with the help of highlights and selection, instruments present in this tool. The data obtained from the interviews were explored using the Thematic Content Analysis technique, proposed by Bardin (2011). To compose the data analysis, these were carried out in three phases: pre-analysis; material analysis; and the treatment of results, inference and interpretation. Results: after analysis, three empirical categories emerged: “Feelings and emotions related to the beginning of PDCR”, “Feedback, opportunities for repetition and facilitators” and “Cognitive learning and practical experience”. The students expressed good feelings during the practice, highlighting the transformation process in a positive way, security in working in a small group, achievement of learning by observing other students, relationship of targeted repetitions with their knowledge and feelings, presence of facilitators and the interruption practice for feedback for confidence, security and the importance of articulating theory with practical experience. Conclusion: there was an increase in the participants' self-confidence and confidence in decision-making, increased satisfaction and improved performance in cardiopulmonary resuscitation, in addition to the acquisition of new skills and a positive perception about the presence of the facilitators. Objective and targeted feedback maximized time spent practicing resuscitation skills, contributing to mastery of a given skill.